2019
DOI: 10.3892/or.2019.7420
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma growth suppression by riluzole delivery via iron oxide nanocage in nude mice

Abstract: Osteosarcomas are the most commonly occurring malignant bone cancer in young individuals. The survival rate of patients with metastatic osteosarcoma is low and has been stagnant for over two decades. We previously demonstrated that the glutamate release inhibitor, riluzole inhibits osteosarcoma cell growth. Towards the development of more effective therapy, we investigated the delivery of riluzole in human metastatic osteosarcoma xenografts in mice. We compared the efficacy of riluzole delivery by intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 40 publications
(50 reference statements)
0
16
0
1
Order By: Relevance
“…e treatments for osteosarcoma include surgery, radiotherapy, chemotherapy, or a combination of modalities. Despite improvements in diagnostic and therapeutic techniques, the 5-year survival rates for patients with osteosarcoma have not increased over the last 20 years [3,4]. e potentially high incidence of morbidity and low cure rate urgently require novel methods for diagnosing and treatments which rely on biomedical research.…”
mentioning
confidence: 99%
“…e treatments for osteosarcoma include surgery, radiotherapy, chemotherapy, or a combination of modalities. Despite improvements in diagnostic and therapeutic techniques, the 5-year survival rates for patients with osteosarcoma have not increased over the last 20 years [3,4]. e potentially high incidence of morbidity and low cure rate urgently require novel methods for diagnosing and treatments which rely on biomedical research.…”
mentioning
confidence: 99%
“…Riluzole-mediated YAP and P73 complex was reported to activate Bax promoter to regulate pro-apoptotic activity (55). Previous studies by our group also suggested that iron oxide nanoparticle-delivered riluzole induced apoptosis in vitro in osteosarcoma cells and shrunk osteosarcoma tumors in a xenograft mouse model (72,73). Since apoptosis ultimately leads to the elimination of cancer cells, a better understanding of the induction of riluzole-mediated cell death, the effects of riluzole on different cellular processes and how they are related to apoptosis may further improve the use of riluzole in different cancer types.…”
Section: Riluzole Induces Apoptosismentioning
confidence: 65%
“…Although Riluzole induces apoptosis in osteosarcoma in the xenograft mouse model, it needs to be determined if Riluzole activates c-Abl kinase and phosphorylates YAP at Y357 to induce apoptosis in vivo 58 . Riluzole has been shown to induce apoptosis through ER stress in prostate cancer cell lines 15 .…”
Section: Discussionmentioning
confidence: 99%